Artistic Conceptualization of Power in William Wordsworth’s Poetry - Romanyshyn, Nataliia (2022)
This article discusses the specificity of poetic conceptualization of power in the poetry of William Wordsworth. Thefocus is on the diversity of textual images of a human being in general, such as an individual or collective subject,and on the philosophical concepts of human life and destiny positioned by the authors in the centre of artisticreflection synthesizing the appropriate social pragmatics. The research is based on the cognitive-discursive approachand proceeds from the scientific ideas about the dynamics of correlation between the cultural-historical paradigmand artistic thinking, the cognitive power of artistic image and artistic text as a linguistic sign of national culture.It involves the integration of research tools of linguistic and cognitive stylistics, cultural and literary studies, whichbuilds a vector of analysis from the concept of power as a social phenomenon to its embodiment, explicit andimplicit, at different levels of textual matter.
Keywords: Wordsworth, William